Destabilization of Soil Carbon After Saltwater Intrusion in Coastal Agricultural Soils - Kalu, Subin; Ricker, Matthew C.; Janson, Julia; Nordlund, Dennis; Li, Hui (Environmental science & technology, 2025)
Saltwater intrusion (SWI) is a concerning issue impacting agricultural production and soil C cycling, which can have a wider effect on the climate. Complex soil processes driving soil C cycling following saltwater intrusion have not yet been fully quantified. Agricultural fields with varying degrees of saltwater intrusion, unaffected control, and native tidal marsh were studied to understand the impacts of saltwater intrusion on soil properties and soil carbon dynamics. SWI increased soil EC and decreased the nutrient-holding capacity, affecting crop production. SWI promoted the loss of water-soluble labile SOC, which was found to be linked to the destabilization of the labile SOC associated with poorly crystalline Fe-oxides. This destabilization potentially resulted from the reductive dissolution of poorly crystalline Fe-oxides caused by fluctuating redox conditions following the periodic saltwater intrusion. Our findings highlight the urgent need to explore management strategies that can prevent the loss of SOC and mitigate the negative impacts of saltwater intrusion in coastal agriculture, as the issue of saltwater intrusion is expected to increase over the next century.